An Elucidation on Veneration of Prophet Muhammad Peace be Upon Him: Lesson for Muslims - Muhammad, Usman Jimoh (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2025)
This paper explores the exalted position of Prophet Muhammad peace be upon him in the sight of Allah. The article adopts the literature approach in exposition of the points. To authenticate the position of the paper, it solemnly relies on the Glorious Qur’an and prophetic traditions in addition to few other sources. The discussion highlights Prophet’s glorification above all creation, the levitation of his fame by Allah, the swift respond to his demands by Allah and the unwavering support for his dignity. The paper also looks into the magnitude of Allah’s love for the Prophet, his sanctified being, and unique corporeal formation as evidences solidifying his esteemed position. The paper enunciates some derivable lessons for Muslim from veneration of the Prophet. The paper recommends Muslims should abstain from any form of denigration of the personality of the Noble Prophet and his household and learn more about his rights so as to accord him his due respect. In addition, Muslims should exhibit true love for the Prophet, uphold his teachings and send much salutations on him. [Artikel ini mengkaji kedudukan mulia Nabi Muhammad Saw di sisi Allah. Penelitian ini menggunakan metode tinjauan pustaka dalam mengumpulkan data yang relevan serta menganalisisnya secara tepat. Untuk menguatkan argumen dalam kajian ini, penelitian ini secara utama merujuk pada Al-Qur’an dan hadis Nabi, serta beberapa sumber lainnya. Pembahasan dalam makalah ini menyoroti pemuliaan Nabi di atas seluruh makhluk, pengangkatan namanya oleh Allah, respons cepat terhadap permohonannya, serta dukungan Allah yang tak tergoyahkan terhadap kehormatannya. Selain itu, penelitian ini juga mengulas besarnya cinta Allah kepada Nabi, kesucian pribadinya, serta keunikan bentuk jasmaninya sebagai bukti yang memperkokoh kedudukannya yang agung. Makalah ini juga mengemukakan berbagai pelajaran yang dapat diambil oleh umat Islam dari penghormatan terhadap Nabi. Temuan penelitian menunjukkan bahwa dalam pandangan Allah, Nabi Muhammad Saw menempati posisi kehormatan yang tiada bandingannya. Selain itu, berbagai dalil Al-Qur’an dan hadis menegaskan kewajiban umat Islam untuk memberikan penghormatan, rasa hormat, dan pengagungan terhadap beliau].